Multi-environment analysis of grain yield in a diverse set of bread wheat genotypes - Singh, Charan -; Gupta, Arun; Kumar, Pradeep; Ramdas, Sendhil; Krishnappa, Gopalareddy; Gupta, Vikas; Singh, Sanjay Kumar; Sharma, Amit Kumar; Tyagi, Bhudeva Singh; Singh, Gyanendra; Chatrath, Ravish; Singh, Gyanendra Pratap (Journal of Cereal Research, 2025)
A diverse set of 50 high yielding bread wheat genotypes were evaluated at 16 different locations belongs to 4 major wheat growing zones of India during 2016-17.The genotypes were planted in an alpha lattice design with two replicates per genotype and six rows of 3m length per replication with a plant-to-plant distance of 10cm and row-to-row distance of 25cm (gross plot size of 4.5 m2). Grain yield from 4 middle rows was measured with a net plot size of 3.2 m2 was converted into ton ha-1. The yield data was analyzed by the stability models, Eberhart and Russel (1966), AMMI and GGE biplot. The result shows that the genotypes i.e. G14 and G26 were the most stable genotypes in Eberhart and Russel (1966) model of stability analysis whereas; G10, G14, G18, G23, G26, G30, and G47 were found out to be stable in AMMI stability model. Stable genotypes in GGE model are G26, G23, G10, G43 and G14. In overall, G14 and G26 were turned out to be the most stable genotypes according to these three stability models. The GGE bi-plot indicated that Durgapura location was observed as an ideal environment followed by Hisar, Ludhiana, Delhi, Pantnagar and Powerkheda that can be recommended for the study of bread wheat. The G48 ranked best for (Durgapura and Pantnagar); G29 (Powarkheda) and G35 (Hisar, Delhi and Ludhiana) based on grain yield performance. In comparison, Durgapura was observed as an ideal and representative environment for studying yield stability in bread wheat. DOI.10.25174/2582-2675/2020/92977